IP-centric control and management of optical transport networks. - Bernstein, G.M.
Previous techniques for the management and control of optical transport networks are proving inadequate in today's rapidly evolving multivendor environments. This article examines the issues and challenges involved in developing a standardized optical network control plane. The control of optical transport networks is decomposed into provisioning models, a circuit provisioning process based on signaling, a neighbor and service discovery process, and a topology and resource discovery process. Unique properties and challenges of optical transport networks are explained in the context of these functions
Keywords: IP-centric control; Circuit provisioning; Management; Neighbor discovery process; Optical transport networks; Provisioning models; Resource discovery process; Service discovery process; Signaling; Standardized optical network control plane; Topology process